Food safety and quality training: The use of a lateral flow immunochromatographic strip test for rapid detection of pesticide residue on leafy vegetables - Prabakusuma, Adhita Sri; Santosa, Budi (Universitas Ahmad Dahlan, 2023)
Ensuring the safety and quality of leafy vegetables, especially by controlling any traces of pesticides, is crucial for maintaining human health. This international community service program was designed to expand the vocational knowledge and skills of the people of Timor-Leste in using lateral flow immunochromatographic strip tests for quickly detecting pesticide residue on leafy vegetables. The program was organized by UAD in partnership with PCIM Timor-Leste and the An-Nur Islamic Foundation. The program included several stages, including preparation, coordination, consolidation, implementation, monitoring, and evaluation. The participants’ knowledge of food safety and food hygiene increased significantly from 52% prior to training to 96% after the training. Moreover, the ability to detect pesticide contamination in vegetables using LFI technology improved by 84%, rising from just 8% before training to 92% after training. All participants expressed interest in the UAD in Timor-Leste's future continuation of this training program.